Pengembangan Modul PPKn Berbasis Masalah pada Materi Norma dan Keadilan Siswa Kelas VII SMP - Tamami, Siti (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2020)
This study aimed to produce a problem-based Pancasila and Civic Education Module that was feasible, interesting, and effective to use. The study used the Borg and Gall developmental research model. The trial subjects in this study was VII grade students of the Laboratory Junior High School of State University of Malang (UM). The results of the validity test of material experts gained an average of 88%, media experts by 78%, and learning experts by 80%. From the small group trial results obtained questionnaire data filling by students an average of 86%, while from the large group an average of 91%, the average competency test results were 83, with grade completeness of 90.62%. In conclusion, the problem-based PPKn module on Norms and Justice Material had been feasible, interesting, and effective for use in VII grade students of junior high school who have a variety of abilities.